2009
DOI: 10.1159/000222783
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Subthalamic Stimulation and Medication on Proximal and Distal Bradykinesia in Parkinson’s Disease

Abstract: Objective: To evaluate the usefulness of a new instrument for bedside testing of proximal arm and distal finger tapping performance in patients with Parkinson’s disease (PD). Methods: Twenty healthy controls and 25 PD patients with subthalamic nucleus deep brain stimulation were investigated in different treatment conditions using three different tapping paradigms: (1) the standard tapping task of the CAPSIT-PD-protocol; (2) alternate pressing of two buttons on the new board by moving the arm at the elbow and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Moreover, the most proximal movement in that study involved manipulation of the elbow joint, rather than the shoulder. Similarly, other tapping tasks [10] have a repetitive, rhythmic component that might impact on performance. In contrast, Dafotakis et al [11] showed distal (finger tapping) and proximal (horizontal pointing) movements being similarly improved by STN-DBS when performed separately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the most proximal movement in that study involved manipulation of the elbow joint, rather than the shoulder. Similarly, other tapping tasks [10] have a repetitive, rhythmic component that might impact on performance. In contrast, Dafotakis et al [11] showed distal (finger tapping) and proximal (horizontal pointing) movements being similarly improved by STN-DBS when performed separately.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are supported by data from a grip lift task [9] demonstrating benefit during the early grip phase under L-Dopa but greater improvement in the late, proximal phase for STN-DBS while off medication. Furthermore, Potter-Nerger et al [10] showed significant improvement in distal (finger) and proximal (elbow and shoulder) repetitive movements under STN-DBS, but with a greater impact on proximal compared with distal tapping. Contrasting evidence is presented by Dafotakis et al [11] who demonstrate that STN-DBS improved equally the kinematics of simple finger tapping and horizontal pointing movements.…”
Section: Introductionmentioning
confidence: 98%
“…One group of patients performed tapping test [48] that is frequently used by neurologists to examine hand movements in PD patients. The test consists of the proximal and distal tapping tasks using a specially designed board (▶ Figure 4) as the one proposed in [48]. The proximal tapping task refers to the alternate pressing of two large buttons located 20 cm apart with the palm of the hand during 30 seconds.…”
Section: Rehabmentioning
confidence: 99%
“…Since the clinical scales are designed for disease stage assessment, the correlation analysis is performed only for the sensor glove data MPIs. The correlation analysis is carried out between the proposed hand MPIs (▶ Figure 12) and tapping test [48] and UPDRS-III clinical scale [3]. The tapping-test is performed by patients while UPDRS-III values result from the neurologist's evaluation.…”
Section: Correlations With Clinical Scalesmentioning
confidence: 99%
“…The experimental protocol, designed by the movement disorder specialists (Table 1 ; Figure 1 ), includes six exercises performed with the left and right hand: four arm/hand movements and two tapping test movements, well-established experimental paradigm designed for bradykinesia assessment ( 30 ). The tested movements are chosen to closely reflect the patient’s activities of daily living that engage forearm muscles.…”
Section: Methodsmentioning
confidence: 99%